PENURUNAN DERAJAT KEASAMAN SALIVA PADA ANAK USIA 10-12 TAHUN YANG MENGKONSUMSI COKELAT HITAM SUKROSA, XYLITOL, DAN STEVIA - Kaswindiarti, Septriyani; Saputra, Muhammad Rhaufly Dwi Arga; Yudiatna, Clara Cessa Putri; Widianto, Shafwan Rafif; Muhammad, Dimas Rahadian Aji; Praseptiangga, Danar; Murdiyanto, Dendy; Sari, Nendika Dyah Ayu Murika; Mardiyati, Nur Lathifah (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Chocolate is a widely consumed food, particularly by children. It is often considered a contributing factor to the development of dental caries due to its high sugar content, which can lead to the formation of dental caries. Aim: This study aimed to determine whether consuming dark chocolate sweetened with sucrose, xylitol, and stevia would reduce saliva acidity in children aged 10-12 years. Methods: Twenty-one children aged 10-12 years were given dark chocolate with three sweeteners: 30% sucrose, 30% xylitol, and 1% stevia. The subjects' saliva was collected 10 minutes after chewing chocolate with sucrose on day 1, chocolate with xylitol on day 2, and chocolate with stevia on day 3 for 30 seconds and then measured by a pH meter. The measurement was repeated thrice. Result: The difference in mean saliva pH before and after treatment with the three types of chocolate were analysed using the One-way ANOVA test.  A decline in pH was observed in all treatment groups; however, the most significant decrease was observed in the sucrose chocolate group (0.34 ± 0.12), followed by the stevia chocolate group (0.26 ± 0.09), and the least significant decrease was observed in the xylitol chocolate group (0.14 ± 0.07). Conclusion: A statistically significant difference was observed in the decrease in saliva acidity among children aged 10-12 years who consumed dark chocolate containing sucrose, xylitol, and stevia